La pobreza de tiempo. Una revisión metodológica - Damián, Araceli (El Colegio de México A.C., 2003)
If the minimum level of consumption for not being poor requires both money and domestic production, then official poverty standards fail to measure household needs correctly. The aim of this article is to analyze the way measuring the time required for domestic chores, work outside the home, personal care and grooming and leisure has been incorporated into the calculation of poverty. The author analyzes the parameters used for calculating the poverty of time contained in the index of excessive work time that forms part of the method for the integrated measurement of poverty. To this end, she has compared other methods of measuring poverty and contrasted the standards of this index with social practices observed through household income and expenditure surveys, the 1996 time use model and the National Employment Survey. After carrying out the assessment and highlighting the need to consider time in the measurement of poverty, the author shows the changes in the structure of poverty once poverty of time has been calculated and combined with th poverty of income.